Activity of Estrogen Receptor β Agonists in Therapy-Resistant Estrogen Receptor-Positive Breast Cancer - Datta, Jharna; Willingham, Natalie; Manouchehri, Jasmine M.; Schnell, Patrick; Sheth, Mirisha; David, Joel J.; Kassem, Mahmoud; Wilson, Tyler A.; Radomska, Hanna S.; Coss, Christopher C.; Bennett, Chad E.; Ganju, Ramesh K.; et al. (Frontiers in Oncology, 2022)
Background: Among women, breast cancer is the leading cause of cancer-related death worldwide. Estrogen receptor α positive (ERα+) breast cancer accounts for 70% of all breast cancer subtypes. Although ERα+ breast cancer initially responds to estrogen deprivation or blockade, resistance emergence compelling the use of more aggressive therapies. While ERα is a driver in ERα+ breast cancer, ERβ plays an inhibitory role in several different cancer types. To date, the lack of highly selective ERβ agonists without ERα activity has limited the exploration of ERβ activation as a strategy for ERα+ breast cancer. Methods: We measured expression levels of ESR1 and ESR2 genes in immortalized mammary epithelial cells and different breast cancer cell lines. The viability of ERα+ breast cancer cell lines upon treatments with specific ERβ agonists, including OSU-ERb-12 and LY500307 was assessed. The specificity of the ERβ agonists, OSU-ERb-12 and LY500307, was confirmed by reporter assays. The effects of the agonists on cell proliferation, cell cycle, apoptosis, colony formation, cell migration, and expression of tumor suppressor proteins were analyzed. The expression of ESR2 and genes containing ERE-AP1 composite response elements was examined in ERα+ human breast cancer samples to determine the correlation between ESR2 expression and overall survival and that of putative ESR2 regulated genes. Results: In this study, we demonstrate the efficacy of highly selective ERβ agonists in ERα+ breast cancer cell lines and drug-resistant derivatives. ERβ agonists blocked cell proliferation, migration and colony formation; and induced apoptosis and S and/or G2/M cell cycle arrest of ERα+ breast cancer cell lines. Also, increases in the expression of the key tumor suppressors FOXO1 and FOXO3a were noted. Importantly, the strong synergy between ERβ agonists and ERα antagonists suggested that the efficacy of ERβ agonists is maximized by combination with ERα blockade. Lastly, ESR2 (ERβ gene) expression was negatively correlated with ESR1 (ERα gene) and CCND1 RNA expression in human metastatic ER+/HER2- breast cancer samples. Conclusion: Our results demonstrate that highly selective ERβ agonists attenuate the viability of ERα+ breast cancer cell lines in vitro and suggest that this therapeutic strategy merits further evaluation for ERα+ breast cancer.